SCAR (Sequence Characterized Amplified Region) Analysis for Pi-b and Pi-ta genes on 28 Genotypes of Rice - , Sobir; , Santoso; Hajrial Aswidinnoor; Mukelar Amir (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2005)
Evaluation to blast disease (Pyricularia grisea) resistance was carried out by using two SCAR (Sequence Characterized Amplified Region) markers of Pi-b and Pi-ta blast resistance genes, and spray-inoculation method with 10 races of P. grisea on 28 paddy genotypes, that consisted six wild genotypes of rice. The results revealed that among 28 paddy genotypes, fifteen genotypes carrying both genes including Oryza rufipogon; six genotypes carrying Pi-b genes including O. alta, two genotypes carrying Pi-ta gene, and five genotypes did not possess both gene including O. glumaepatula, O. officinalis, O. latifolia, and O. malapuzhaensis. Based on infection intensity, the evaluated genotypes were vary in responses to different ten races of P. grisea, indicated that the evaluated genotypes were vary in carrying Pi genes. Analysis in detail indicated that existence of Pi-ta gene associated with lower infection intensity caused by P. grisea race 063 C. Keywords: SCAR markers, rice blast resistance, Pyricularia grisea